Faster [videorecording (DVD)] - Tillman, George, 1969-; Johnson, Dwayne, 1972-; Thornton, Billy Bob; Jackson-Cohen, Oliver, 1986- (Sony Pictures Home Entertainment, 2011)
After ten years in prison, Driver (Dwayne Johnson) has focused on one thing -- hunting down the people responsible for brutally murdering his brother. Now a free man with a terrifying purpose, he sets out to find and kill all those on his list. But on his heels are two men who will do anything to stop him -- a veteran cop (Billy Bob Thornton) and a hitman (Oliver Jackson-Cohen) who finds his match in this worthy opponent. Now, the hunter is also the hunted.